THE U.S. AS THE NEW ROME: DISPUTING THE NEW WORLD ORDER - O. I. Ivonina (Сравнительная политика)
The starting point of the conclusions of politicians and experts was the recognition of the changed nature of threats to the New World Order. In post-Westfalia system of international relations the main actors are not sovereigns, but transnational actors of world politics, including transnational terrorist and criminal networks. In this situation, the support of global security threat serves the underground world – terrorists, shady business structures, failed states. The unconventional nature of the threat to peace and stability of the New World Order requires an equally innovative response which transcends the formal constraints of international law and the traditional doctrine of deterrence. An analysis of the U.S. foreign policy concepts suggests that today’s academic and political community has promoted consensus of neoliberals and neoconservatives, supporters of the institutional functionalism and representatives of the school of Realpolitik. This consensus was based on the recognition of the admissibility of pre-emptive strikes on the territory of failed states, sponsoring international terrorism, or the implementation of open interference in the internal affairs of “rogue states” for human rights and democratic freedoms guarantee.